Impact of Hypertension on Cognitive Decline and Dementia - Naing, Han Lin (Ann Geriatr Med Res, 2020)
Dementia reduces a person’s ability to perform their activities of daily living and is the leading cause of morbidity worldwide. While most preventive measures are ineffective in reducing dementia risk, active treatment of hypertension in middle-aged and older adults without dementia may reduce the incidence of dementia. Hypertension is associated with vascular dementia but may also affect the manifestations of Alzheimer disease. Observational studies support the association between hypertension and white matter lesions, hippocampal atrophy, and cognitive decline. Both increased and decreased blood pressure were related to the development of white matter lesions. Cohort studies showed that hypertension treatment and treatment duration were associated with lower cognitive decline. This review describes findings from randomized controlled studies on the effects of antihypertensives on cognitive decline. Only the Systolic Hypertension in Europe (Syst-Eur) trial using calcium-channel blockers demonstrated a significant reduction in dementia incidence. Further studies are required to evaluate the long-term benefits of antihypertensive treatment in dementia.